China’s influence on Kazakhstan’s economic cooperation with Central Asian countries - L. A. Medukhanova; Z. A. Seriyeva (Экономика: стратегия и практика)
Currently, China, as the largest economic power, exerts a powerful influence on neighboring countries in the region on various aspects of regional and international interaction: from military issues to economic cooperation. One of these regions is Central Asia( CA), which has become an important target for China’s plans in the last decade in the light of the implementation of its foreign economic strategy. Kazakhstan, in turn, being the largest economy in Central Asia, is also aimed at developing regional economic cooperation with other countries in the region: Uzbekistan, Kyrgyzstan, Tajikistan and Turkmenistan. At the same time, the economy of all Central Asian countries, and especially Kazakhstan itself, is strongly influenced by China’s projects aimed at interacting with them. Among these projects, the most important place is occupied by the «one belt one road» project, the Asian infrastructure investment Bank, the silk road Fund, etc. created in connection with it. The purpose of the article is to identify the impact of China’s projects in Central Asia on the development of economic cooperation between Kazakhstan and neighboring countries in the Central Asian region. To achieve this goal, we used such methods of analytical and statistical research as analysis of foreign and domestic publications on the topic under study, statistical data describing the economy and foreign trade of China and Central Asian countries. China, which is currently a major player in the economy of Central Asian countries and especially for Kazakhstan, has an additional, both positive and negative impact on Kazakhstan’s strategic economic cooperation with other Central Asian countries.